RETAINING WALL PLANNING IN WASTE MANAGEMENT - P., Adz-Dzyikri Apriliansyah; Rendiansyah, Inggy; F., Ridho Naufal; Firmanto, Arief (Ridwan Institute, 2024)
This study aims to analyze the performance and productivity of heavy equipment as well as the volume of waste produced in a waste disposal area (TPSA) located in Kuningan Regency. The research was carried out at the Ciniru TPSA located in Jalaksana District, Kuningang Regency, with the aim of finding out the data on the volumes of waste, transport trucks, and excavator heavy equipment. The results show that the amount of existing waste in the area reaches 630 m3 with an average amount of irritation of 71 times per day. In addition, the production of heavy machinery for garbage trucks, excavators, and bulldozers reaches 128.07 m3/hour, which is a working time of 8 hours and operational costs of Rp 244,957/hour, respectively. The findings of this study offer valuable information on the effectiveness of retaining walls in mitigating environmental impact, protecting agricultural areas, and improving waste handling practices. Moreover, investigating methods to extend landfill lifespan through improved spatial planning and capacity forecasting will be crucial, especially for regions facing waste overflow challenges in the near future.